An Investigation of the Diversification Roles of Contractor - Nur Azila Adros; Dr. Nazirah Zainul Abidin (SEISENSE (PRIVATE) LIMITED, 2019)
The construction industry is facing a period of change due to the revolution of new technology, emphasis on strategic alliances and demanding customers. As one of the key players in the construction industry, the contractors play an important role in the development of the construction industry. They are known for their traditional roles during the construction stage by managing and production on site. Due to changes in the industry, the contractors’ role has been evolving during the years, this has impacted their roles to change as well. This paper reviews the traditional roles of the contractor and discusses the reasons for their evolving roles in the construction industry. Finally, this paper delves into the various diversification roles of the contractor in Malaysia which are categorised into two such as the management and technical.